The Influence of Urbanization and Socio-Economic Conditions to Vehicle Ownership in Developing City - Kusuma, Candra Aji; Multifiah, Multifiah; Syafitri, Wildan (Jurnal Bina Praja, 2018)
Malang is a thriving city and destination of migration from rural areas. Vehicle ownership is one indicator of prosperity, but it has a negative effect on city traffic. In 2017 the city of Malang was the third most traffic jam city in Indonesia. This study used the 2016 National Socioeconomic Survey and aimed to see the influence of urbanization and socioeconomic conditions on the preference of owning a vehicle. Income is considered as a budget constraint to the ability to buy a vehicle and is related to the socio-economic conditions of each person. This study used an ordered probit method to measure the level of prosperity with 4 levels of output; those who have no vehicle, who owned at least one motorcycle, who owned at least one car, and who owned at least one car and one motorcycle. The result of the study showed that migration has a negative effect on vehicle ownership. While age has no significant effect, other socio-economic factors have a significant effect. The highest level of vehicle ownership in Malang Raya was one motorcycle, which means that the community in developing cities like Malang Raya was classified as a middle class. This study might be used by the government of Malang to control the growth of vehicles, by considering population growth and socio-economic conditions, to reduce the congestion problem in Malang Raya.